The Accuracy of ICD-10 Codes for Clinical Diagnosis and Supporting Examinations of Hypertension Cases in Inpatient Care at Hospital - Agustina; Meilany, lilik; Muh Erwin Rosyadi; Rosana Dwiyanti Putri; Ruslan Agussalim; Jeny Rezkysadin Ilyas (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Accurate diagnosis coding is essential to support processes such as the preparation of statistical reports, health insurance claims to BPJS, and data-based decision-making. A preliminary study at RSUD X Makassar in the first quarter of 2025 found 243 electronic medical records of inpatients diagnosed with hypertension with diabetes mellitus complications, of which 20 records contained incorrect codes. Objective: To determine the relationship between clinical diagnosis and supporting examinations with the accuracy of ICD-10 codes in hypertension cases among inpatients at RSUD X Makassar. Methods: This study employed a cross-sectional design with a quantitative approach. The population consisted of inpatient medical records from the first quarter, with a sample of 71 medical records of hypertension cases selected using random sampling. Results: Based on hypothesis testing, two variables were analyzed: clinical diagnosis and ICD-10 code accuracy. The significance value (p-value) was 0.184. Since the significance value of 0.184 > 0.05, the next variable tested was the completeness of supporting examinations and code accuracy, which yielded a significance value of 0.452 > 0.05. Further Pearson correlation testing revealed that the strength of the relationship between clinical diagnosis and code accuracy had a correlation coefficient of r = 0.158 with a significance value of p = 0.189 (p > 0.05). Meanwhile, the relationship between completeness of examinations and code accuracy showed a correlation coefficient of r = 0.089 with a significance value of p = 0.459 (p > 0.05), indicating a very weak correlation. Conclusion: Both variables demonstrated no significant relationship, suggesting that other factors may be more dominant. The experience and training of coders may have a greater influence than the completeness of medical records. Moreover, the implementation of health information technology could further enhance coding accuracy. Keyword: Code Accuracy, Clinical Diagnosis, Supporting Investigation